KNOWLEDGE AND ATTITUDE REGARDING ORAL CANCER AMONG DENTAL PRACTITIONERS IN BANDA ACEH: A CROSS-SECTIONAL STUDY - Yuli Fatzia Ossa; Nova Rosdiana; Chairunnas Chairunnas; Sarah Listia Rani (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Oral cancer remains a global health concern. Many cases are diagnosed at an advanced stage, which affects both treatment outcomes and prognosis. Objective: This study aims to assess the knowledge and attitudes of dental practitioners toward oral cancer in Banda Aceh. Methods: A cross-sectional study was conducted in 2023 among dentists in Banda Aceh and its surrounding areas. Data were collected using an online questionnaire, which included demographic information and questions on etiology, risk factors, signs and symptoms, oral screening, and attitudes toward oral cancer. Results: A total of 130 respondents participated, comprising 87.7% general practitioners and 12.3% dental specialists. More than half of the respondents demonstrated good knowledge of oral cancer etiology (61.5%) and its signs and symptoms (63.8%). However, only 52.3% had ever performed oral screening. Among those who had never conducted oral screening, 74.6% cited a lack of knowledge on how to perform it, with 16.9% specifically stating that they did not know the correct procedure. Additionally, only 40% of respondents had attended an oral cancer-related conference in the past year. A significant association was found between gender and knowledge of etiology (p < 0.001). Conclusion: To reduce the burden of oral cancer, it is essential to implement strategies that enhance dental practitioners’ knowledge and attitudes toward the disease. Early detection through oral screening and participation in training programs can effectively minimize delays in diagnosis and improve patient outcomes.